(untitled) (International Journal of Engineering and Computer Science, 2018)
In this paper we have studied about issues related to authenticity, integrity and security of data storage in cloud data centres. Security in cloud is under scanner due to which its adoption by IT sector is in slow stride. Using Cloud Storage, users can remotely store their data at less cost per byte and access services with high quality from a shared pool of configurable computing resources, without Operational Expenditure and Capital Expenditure. In cloud environment client’s data is stored outside the organization premises which make client insecure regarding his data at cloud storage facility as it may be accessed and modified by unauthorized users. So in this paper we have proposed a model Securing Cloud Data using Key as a Service (SCDKS) which will provide authenticity for accessing data at storage by providing keys to access file/data. CSP will authenticate every user by generating keys by Key as a Service (KaaS), KaaS will generate a unique key for every session dynamically when user wants to access data at cloud. Since key is generated for each session it cannot be used by other users or data cannot be accessed by them which ensure security, integrity to data. A sophisticated and threshold key generation algorithm is used in KaaS for generating keys for users after authenticated by Cloud Service provider.